2013
DOI: 10.1111/1759-7714.12063
|View full text |Cite
|
Sign up to set email alerts
|

Huge primary malignant melanoma of the esophagus: A case report and literature review

Abstract: KeywordsClinical features; immuno-histochemistry; pathological features; primary malignant melanoma of the esophagus (PMME); surgical treatment. Correspondence AbstractPrimary malignant melanoma of the esophagus (PMME) is a relatively rare esophageal malignancy accounting for 0.1-0.2% of all esophageal tumors. Because the tumor cells occur mainly in the esophagus mucosa and grow along the longitudinal axis in the lumen, it causes relatively late obstruction symptoms, even though the lesion is a much larger ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…In developing countries oesophageal cancer makes up approximately 80% of total cases and deaths (11,12). Oesophageal cancer histological type and its incidence differs depending on geographic locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries oesophageal cancer makes up approximately 80% of total cases and deaths (11,12). Oesophageal cancer histological type and its incidence differs depending on geographic locations.…”
Section: Introductionmentioning
confidence: 99%
“…This data indicates that males are more affected than females in both well-developed and developing countries. The relative risk factors for developing oesophageal cancer depend on geographic locations as well as variations in histological types (Table II) (11,13).…”
Section: Introductionmentioning
confidence: 99%
“…From 2013 to 2016, other 35 cases of PMME were reported in literature [ 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 ] with a particular emphasis about the case presented by Zhang et al [ 228 ] that measured 12 cm (huge PMME).…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al reported a median disease-free survival of 5.9 months for 70 resected cases [3], and Wang et al reported a median relapse-free survival (RFS) of 4.5 months for 58 resected cases [1], indicating that the prognosis for resected cases was also poor. Although many papers, including our previous report [10], have reported on resection as the initial treatment of PMME, there are few reports describing treatment after recurrence [6][7][8][11][12][13][14]. According to previous reports, recurrence sites vary widely, and treatments such as surgery, chemotherapy, radiation therapy, and immunotherapy are used.…”
Section: Discussionmentioning
confidence: 99%